1979
DOI: 10.2323/jgam.25.127
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Urease and Extracellular Dnase in Yeast Species

Abstract: Urease and extracellular DNase activities were tested in 292 strains belonging to 125 species of 33 genera. Basidiomycetous yeasts and related species had both urease and extracellular DNase. Species belonging to the genera Rhodotorula and Cryptococcus, and four species of Candida (Candida curvata, Candida humicola, Candida bogoriensis, and Candida diffluens) which are considered to be closely related to basidiomycetous yeasts, showed both activities. In general, ascosporogenous yeasts and their imperfect form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Previous studies have shown that extracellular enzyme production is common in basidiomycetous yeasts (8,20). Our results support the observation by van der Walt et al (22) that some ascomycetous yeasts, such as Saccharomycopsis spp., also produce extracellular enzymes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Previous studies have shown that extracellular enzyme production is common in basidiomycetous yeasts (8,20). Our results support the observation by van der Walt et al (22) that some ascomycetous yeasts, such as Saccharomycopsis spp., also produce extracellular enzymes.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, the use of the DBB test is not widespread. This report describes an improved DBB test to detect basidiomycetous relationships of yeasts and yeastlike organisms and correlates the results of the DBB test with extracellular enzyme production.(DBB) (2,3,6,8,9,11,14,17,(20)(21)(22) 26; C. E. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of extracellular deoxyribonuclease (DNase) was determined by the method of SEN and KoMAGATA (19). The Diazonium Blue B (DBB) color test was performed according to the methods of VAN DER WALT and HoPsu-HAVV (20) and HAGLER and AHEARN (21).…”
mentioning
confidence: 99%
“…This yeast named Candida acutus was characterized by the morphological properties of the formation of septated or short mycelical cells and budding cells from tapering base on lateral of cells in ring or pellicle on YM broth, and the biochemical properties of a high GC content (54.7 %), the positive activities of urease and DNase, and the Q9 of coenzyme Q system. In the phylogenetic relationship of Candida, Torulopsis, and other anasporogenous yeasts on the basis of biochemical characters, NAKASE and KOMAGATA (7) and SEN and KOMAGATA (8) pointed out that yeasts with high GC content (above 50%) and activities of urease and extracellular DNase would originate from heterobasidiomycetes. From this point of view, C. acutus is considered to be related to heterobasidiomycetes, though its perfect stage is not found yet.…”
Section: Resultsmentioning
confidence: 99%